2021
DOI: 10.1007/s10064-021-02492-z
|View full text |Cite
|
Sign up to set email alerts
|

Failure characteristics of shale after being subjected to high temperatures under uniaxial compression

Abstract: Uniaxial compression tests and acoustic emission (AE) monitoring of shale specimens with horizontal and perpendicular bedding planes after being subjected to high temperatures were conducted to investigate the effect of a high-temperature environment on shale failure characteristics. The results reveal that specimens in the two bedding directions experienced severe rockburst failure. The rockburst processes of all the tested specimens were similar and can be divided into two main stages according to the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…29 The AE characteristics of shale can be understood by describing the time-and frequency-domain characteristics of the AE waveform. 30 Previous studies have shown that the AE characteristics of shale are affected by shale properties including pre-existing fracture, 27 fracture geometry, 31 pore structure, 26 mineral composition, water condition, 28 bedding, 32 anisotropy, 33 and external experimental environments (such as temperature, 34 axial stress, 27 confining pressure, 28 and other factors). 35 Fractal theory is an effective approach for investigating the complexity of rock mass fractures based on self-similarity and scale invariance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…29 The AE characteristics of shale can be understood by describing the time-and frequency-domain characteristics of the AE waveform. 30 Previous studies have shown that the AE characteristics of shale are affected by shale properties including pre-existing fracture, 27 fracture geometry, 31 pore structure, 26 mineral composition, water condition, 28 bedding, 32 anisotropy, 33 and external experimental environments (such as temperature, 34 axial stress, 27 confining pressure, 28 and other factors). 35 Fractal theory is an effective approach for investigating the complexity of rock mass fractures based on self-similarity and scale invariance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The depth of the Mponeng mine in South Africa, the deepest mine in the world, has surpassed 4000 m [ 5 ] and as a result of the development of mineral resources in China, mines in the country will reach an underground depth of 1000–2000 m [ 6 , 7 ]. Deep rock mass occurs in a complex environment consisting of a high-stress field, high-temperature field, high permeability–pressure field, fast unloading, and dynamic disturbance caused by hard-rock mining, resulting in frequent disasters [ 8 , 9 , 10 , 11 , 12 ], as shown in Figure 1 . For example, deep mining of the Kaiyang phosphate mine has led to a wide range of loose circles in the rock surrounding the underground engineering owing to the action of high stress; this simultaneously results in decreased rock strength, increased unstable block, and groundwater seepage, which has caused great engineering geological disasters [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature also plays a key role in determining the damage behavior of rock. In a notable study conducted by Huang et al [9], researchers have implemented uniaxial compression tests of shale specimens under a high-temperature environment. Their results indicate that shale specimens with perpendicular bedding planes are more fragile than horizontal bedding planes with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%